The impact of population heterogeneity on factor analysis estimation - Marques, C.; Dias, J. G. (XXI Jornadas de Classificação e Análise de Dados (JOCLAD2014), 2014)
This paper discusses the impact of population heterogeneity on factor analysis under the homogeneity assumption and potential biases resulting from aggregation. An illustration using the Holzinger-Swineford Mental Abilities data shows that the factor mixture model relaxes factor analysis specification taking population heterogeneity and potential outliers into account.